PENGARUH PROSES FRAKSINASI PATI SAGU TERHADAP KARAKTERISTIK FRAKSI AMILOSANYA - Indah Yuliasih, Tun Tedja Irawadi, Illah Sailah, Hardaning Pranamuda, Krisnani Setyowati, Titi Candr (Jurnal Teknologi Industri Pertanian, 2007)
ABSTRACTThe objective of this research is to analyse the effect of the starch suspension temperature and the 1-butanol volume as complexing agent to the characteristic of amylose of sago starch fraction. In the fractionation process, the yield of amylose fraction increased in line with  the increasing of starch suspension temperature and increasing of 1-butanol volume as complexing agent.  The different condition of fractionation process produced  amylose fraction which was different in molecular weight distribution (fraction-1 and fraction-2).  The functional properties of amylose fraction with  fraction-2 dominant (solubility, swelling power and freeze-thaw stability) are relatively lower compared to the amylose fraction with  fraction-1 dominant.  On the other hand  the clarity and oil retention capacity (ORC) value are relatively higher.Key words : fractionation, sago starch, amylose fraction, functional properties